2021
DOI: 10.18632/aging.203166
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of inferior prognostic genes associated with immune signatures and chemotherapy outcome in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a group of heterogeneous hematological malignancies. We identified key genes as ITGAM and lncRNA ITGB2-AS1 through different bioinformatics tools. Furthermore, qPCR was performed to verify the expression level of essential genes in clinical samples. Retrospective research on 179 AML cases was used to investigate the relationship between the expression of ITGAM and the characteristics of AML. The critical gene relationship with immune infiltration in AML was estimated. The clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…6f ). IC-lncRNA ITGB2-AS1 is antisense to ITGB2 and has been shown to be highly expressed, and closely related to immunosuppression in AML 44 . ITGB2-AS1 may be used as a potential immunotherapeutic target in cancers.…”
Section: Resultsmentioning
confidence: 99%
“…6f ). IC-lncRNA ITGB2-AS1 is antisense to ITGB2 and has been shown to be highly expressed, and closely related to immunosuppression in AML 44 . ITGB2-AS1 may be used as a potential immunotherapeutic target in cancers.…”
Section: Resultsmentioning
confidence: 99%
“…The ITGAM also plays an important role in the tumor microenvironment in leukemia cell activation, chemotaxis, and cytotoxicity [19]. Several studies have shown that the positive expression of ITGAM was closely associated with the prognosis of AML patients [20,21]. A previous study indicated that lncRNA ITGB2 was significantly associated with various immune signatures in AML [22].…”
Section: Discussionmentioning
confidence: 99%
“…ITGB2 and ITGAM have tissue specificity on BM [ 2 ] and take part in a portion of vital biological processes. For example, ITGB2 is involved in adhesion, migration of leukocytes [ 36 ] and immune response including NK cell-induced cytotoxicity [ 37 39 ]. From a bioinformatics analysis, ITGAM and ITGB2 were also up-regulated in myeloma and involved in cytokine-cytokine receptor interaction, innate immune response and inflammatory response that were similar to our results [ 40 ].…”
Section: Discussionmentioning
confidence: 99%